ANALISIS MODEL SISTEM KOMPENSASI DALAM MOTIVASI KERJA PADA RUMAH MAKAN MINANG RAYA BOGOR - Priyo Wismantoro; Intan Mezeki (Jurnal Ilmiah Binaniaga, 2007)
Compensation is a reward in forms of money that was given by the head of a company to his/her employees in order the employees to maintain their high motivation to reach the company’s goal. In this research the writer would like to know to what extend the compensation analysis model can increase the motivation of employees at Rumah Makan Minang Raya Bogor. The application of suitable compensation for each employee is the most crucial problem. Therefore, the right handling of the human resource management is needed. If this were done improperly it would lead to a dissatisfaction of the employees. The nature of compensation is to give a base to decide a decision and act to the employee involved in the administration process. The compensation (incentive) for every one is given once in every 3 months by the owner of the restaurant. The incentive is not flat and is based on workload, attendance, and type of job done by employees. The incentive is roughly ranges from 6% to 38% from the monthly compensation. The difference of incentive for each employee is decided on the expertise of each employee. From the results analysis by regression model it can be concluded that there was a significant result between satisfying compensation with the employee’s work motivation as shown by t counted (8.811) is bigger than t table (2.16). This means that X coefficient is significant with the regression equation Y = 12.043 + 0.673 X, if the satisfaction score increases 1 point then the employee’s motivation will increase 0.673. The incentive awarded to the employee as a supplement is aimed at maintaining employees in the long run as an attempt to create comfortable work condition and environment so that the employees can increase their performance.